Sistem Informasi Pemesanan Menu di Early Coffee menggunakan QR code Berbasis Website - Sibagariang, Swono; Susanti, Jenny (Jurnal Mahajana Informasi, 2022)
A coffee shop is a place that is visited to relax or organize and sells drinks and food. In today's era, people want something instant. The early coffee shop consists of 3 employees, namely 2 waiters and 1 cashier. In ordering drinks and food at Early coffee, customers take a long time to order, from queuing to waiting for the waiter to input the order until the order arrives. Likewise, the waiters are quite confused about where to sit because there are no numbers on each table. The menu ordering information system using a website-based QR code is a system that can provide convenience for customers in ordering menus at each table by scanning the QR code using a smartphone camera or scanner. QR code is a type of two-dimensional matrix code developed by Denso Wave in 1994, which aims to convey information quickly and get a fast response. Ordering QR Codes for customers also aims to replace manual input of table numbers and customer names so that the ordering process becomes more effective and efficient as well as easy to use and understand. The data collection methods used to make this application are the direct observation and interview methods. While the system development method used is the waterfall method. The application runs well and is ready to use from the test results using the black box method. By using this system, cashiers or waiters will find it easier to check orders and record order reports. Suggestions from the author are to develop this application by adding a real-time notification feature, doing regular database backups, maintaining data security, and integrating it with existing payment systems.